Anti-skid wear-resistant coating, preparation method thereof and application of anti-skid wear-resistant coating in basketball court

By combining modified epoxy resin and titanium dioxide nanosheets, coatings with anti-slip, flame retardant and antibacterial properties are prepared, which solves the problems of aging and flammable epoxy resin coating and improves the use of basketball courts and safety performance.

CN119242133AActive Publication Date: 2025-01-03WUHAN XINYUKANG ENVIRONMENTAL PROTECTION NEW MATERIAL TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411464128.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-03
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

The existing epoxy resin coating is prone to aging and flammable during use on the basketball court floor, resulting in a degradation of ground performance and lack of anti-slip and flame retardant properties, which poses safety hazards.

Method used

The anti-slip and wear-resistant coating is prepared through specific reaction and treatment methods to increase the resistance of the coating. Fuel, antibacterial and UV resistance.

Benefits of technology

It improves the wear resistance, anti-slip, flame retardant and antibacterial properties of the coating, extends the service life, and provides better anti-UV aging effect in outdoor environments, improving the safety and performance of basketball courts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005092788860000031
    Figure BDA0005092788860000031
  • Figure BDA0005092788860000101
    Figure BDA0005092788860000101
  • Figure BDA0005092788860000111
    Figure BDA0005092788860000111
Patent Text Reader

Abstract

The invention discloses an anti-skid wear-resistant coating, a preparation method thereof and application of the anti-skid wear-resistant coating in a basketball court, and relates to the technical field of coatings. When the antiskid wear-resistant coating is prepared, firstly, epoxy resin is grafted with vinyl diphenylphosphine and then reacts with epichlorohydrin to obtain modified epoxy resin; then, 2, 2 ', 4, 4'-tetrahydroxybenzophenone and chloroacetyl chloride are subjected to a reaction to prepare an ultraviolet absorption monomer, and the aminated titanium dioxide nanosheet, R-1, 1 '-co-2-naphthylamine and the ultraviolet absorption monomer are subjected to a reaction to obtain a modified titanium dioxide nanosheet; finally, the modified epoxy resin, the modified titanium dioxide nanosheets, ceramsite sand, a defoaming agent, a flatting agent, a curing agent and a diluent are mixed to prepare an anti-skid and wear-resistant coating, and the anti-skid and wear-resistant coating is prepared through coating curing of the anti-skid and wear-resistant coating. The prepared anti-skid wear-resistant coating has good anti-skid, wear-resistant, flame-retardant, anti-ultraviolet aging and antibacterial properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, in particular to an anti-skid and wear-resistant coating and a preparation method thereof and application in a basketball court. Background Art

[0002] Epoxy resin coatings have gradually become the preferred material for basketball court floor coatings due to their high strength and wear resistance. During the long-term use of basketball courts, the mechanical properties of the floor coatings often decline due to frequent sports impact and friction. The outdoor basketball court floor coatings are prone to aging due to long-term exposure to sunlight, which will also accelerate the decline in the mechanical properties of the coatings and may even cause cracks and peeling. In addition, in terms of safety, epoxy resin itself is flammable. In some unexpected circumstances, its flammability may cause safety hazards. Once a fire occurs, the combustion of epoxy resin will produce a large amount of thick smoke and toxic gases.

[0003] In order to avoid the problems of epoxy resin coatings such as wear, insufficient UV aging resistance and lack of flame retardancy during use, it is particularly urgent and important to develop a new basketball court floor coating that integrates anti-skid and wear-resistant, UV aging resistance and flame retardancy. Such a coating can not only improve the performance and safety of basketball courts, but also create a healthier and safer sports environment for athletes. Summary of the invention

[0004] The purpose of the present invention is to provide a non-slip and wear-resistant coating and a preparation method thereof and application in a basketball court, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A non-slip wear-resistant coating, characterized in that it is obtained by coating and curing the non-slip wear-resistant coating, wherein the non-slip wear-resistant coating mainly comprises: by weight, 100 parts of modified epoxy resin, 3-4 parts of modified titanium dioxide nanosheets, 2-3 parts of ceramsite sand, 1-2 parts of defoaming agent, 1-2 parts of leveling agent, 22-24 parts of curing agent, and 30-35 parts of diluent.

[0007] As an optimization, the modified epoxy resin is obtained by grafting vinyl diphenylphosphine onto epoxy resin and then reacting with epichlorohydrin.

[0008] As an optimization, the modified titanium dioxide nanosheets are obtained by reacting amino titanium dioxide nanosheets, R-1,1'-bi-2-naphthylamine and ultraviolet absorbing monomers; the ultraviolet absorbing monomers are obtained by reacting 2,2',4,4'-tetrahydroxybenzophenone and chloroacetyl chloride.

[0009] A method for preparing an anti-skid and wear-resistant coating comprises the following preparation steps:

[0010] (1) weighing epoxy resin and vinyl diphenylphosphine in a mass ratio of 1:(0.3-0.4), mixing epoxy resin and propylene glycol methyl ether in a mass ratio of 1:(1.8-2.0) at 110° C. for 3-5 minutes to obtain solution A, mixing vinyl diphenylphosphine, azobisisobutyronitrile, and propylene glycol methyl ether in a mass ratio of 1:(0.06-0.08):(2-3) to obtain solution B, and adding solution B dropwise to solution A at a dropping rate of 1 mL / min. After the addition is completed, the temperature is raised to 115° C., and the reaction is continued for 3-4 hours. The temperature is lowered to 70-80° C., epichlorohydrin in an amount of 0.3-0.4 times the mass of vinyl diphenylphosphine is added, and the reaction is continued for 3-4 hours. The propylene glycol methyl ether is removed by vacuum rotary evaporation to obtain a modified epoxy resin;

[0011] (2) Weighing 2,2',4,4'-tetrahydroxybenzophenone and chloroacetyl chloride in a molar ratio of 1:2, mixing chloroacetyl chloride and tetrahydrofuran in a mass ratio of 1:(20-30) to obtain a chloroacetyl chloride solution, mixing 2,2',4,4'-tetrahydroxybenzophenone, triethylamine, and tetrahydrofuran in a mass ratio of 1:(0.7-0.9):(20-30), and then dropping the chloroacetyl chloride solution at 4-8° C. at a dropping rate of 0.6 mL / min. After the dropwise addition is completed, continuing to react at 4-8° C. for 5-6 hours. After the reaction is completed, adding an ice-water mixture of 80-100 times the mass of 2,2',4,4'-tetrahydroxybenzophenone, filtering, washing with a saturated sodium bicarbonate solution for 3-4 times, and drying at room temperature for 10-12 hours to obtain an ultraviolet absorbing monomer;

[0012] (3) mixing aminated titanium dioxide nanosheets, R-1,1'-bi-2-naphthylamine, ultraviolet absorption monomer, triethylamine, and N,N-dimethylformamide in a mass ratio of 1:(1.5-2):(1.7-1.9):(0.5-0.7):(40-50), heating to 90-95°C, reacting for 4-5 hours, cooling to room temperature, filtering, washing with pure water for 3-4 times, and drying at 60°C for 10-12 hours to obtain modified titanium dioxide nanosheets;

[0013] (4) Weigh the following components by mass: 100 parts of modified epoxy resin, 3-4 parts of modified titanium dioxide nanosheets, 2-3 parts of expanded clay sand, 1-2 parts of defoaming agent, 1-2 parts of leveling agent, 22-24 parts of curing agent, and 30-35 parts of diluent, mix the above components evenly, and apply them on the surface of the substrate using an applicator to obtain a non-slip and wear-resistant coating after curing.

[0014] As an optimization, the preparation method of the amino titanium dioxide nanosheets in step (3) is as follows: tetrabutyl titanate and 36wt% hydrofluoric acid solution are mixed in a volume ratio of 1:(0.12-0.14), reacted in a high-pressure reactor at 180°C for 24h, cooled to room temperature after the reaction, washed with 0.1mol / L sodium hydroxide solution and pure water three times respectively, dried at 80°C for 4-6h, and then placed in a muffle furnace at 400°C for calcination for 2h, and finally passed through a 200-mesh sieve to obtain titanium dioxide nanosheets, titanium dioxide nanosheets, 3-aminopropyl-trimethoxysilane, and anhydrous ethanol in a mass ratio of 1:(0.5-0.7):(50-60), stirred at 40-50°C for 6-8h, filtered and washed with pure water 3-4 times, and dried at 60°C for 6-8h to obtain amino titanium dioxide nanosheets.

[0015] As an optimization, the curing conditions of step (4) are: baking at 80°C for 30 minutes, then heating to 120°C and baking for 30 minutes.

[0016] As an optimization, the coating thickness of the coater in step (4) is 80 μm.

[0017] As an optimization, the epoxy resin model in step (1) is E20.

[0018] As an optimization, the particle size of the ceramsite sand in step (4) is 250-380 μm; the defoaming agent model is DC-65; the leveling agent model is BYK307; the curing agent model is BANCO-905; and the diluent is acetone.

[0019] As an optimization, the reaction process of the ultraviolet absorbing monomer in step (2) is:

[0020]

[0021] The present invention also provides an application of an anti-skid and wear-resistant coating prepared according to the method for preparing the anti-skid and wear-resistant coating in a basketball court.

[0022] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0023] When preparing the anti-skid and wear-resistant coating, the present invention first grafts vinyl diphenylphosphine onto epoxy resin, and then reacts with epichlorohydrin to obtain a modified epoxy resin; then, 2,2',4,4'-tetrahydroxybenzophenone and chloroacetyl chloride are reacted to obtain an ultraviolet absorption monomer, and amino titanium dioxide nanosheets, R-1,1'-bi-2-naphthylamine and the ultraviolet absorption monomer are reacted to obtain a modified titanium dioxide nanosheet; finally, the modified epoxy resin, the modified titanium dioxide nanosheet, ceramsite sand, a defoamer, a leveling agent, a curing agent and a diluent are mixed to obtain an anti-skid and wear-resistant coating, and the anti-skid and wear-resistant coating is coated and cured to obtain an anti-skid and wear-resistant coating.

[0024] First, vinyl diphenylphosphine is grafted onto epoxy resin, and then reacted with epichlorohydrin to obtain a modified epoxy resin. The carbon-carbon double bond on the vinyl diphenylphosphine is grafted onto the side chain of the epoxy resin under the action of an initiator, thereby introducing phosphorus elements with flame retardant function into the epoxy resin, thereby giving the coating flame retardant properties. Epichlorohydrin can not only increase the epoxy group content of the epoxy resin by reacting with phosphorus, but also convert the vinyl diphenylphosphine into a quaternary phosphite structure. The quaternary phosphite molecules can penetrate the cell membrane of bacteria or molds and destroy the structure of the cell membrane, thereby inhibiting or killing microorganisms. Therefore, the presence of the quaternary phosphite structure can give the coating certain antibacterial properties.

[0025] Then, a silane coupling agent is used to make the surface of the titanium dioxide nanosheets have amino groups. Titanium dioxide, as a rigid particle, has high hardness and strong wear resistance, can improve the wear resistance and impact resistance of the coating, and can reflect ultraviolet rays for outdoor use to achieve a certain anti-ultraviolet aging function; 2,2',4,4'-tetrahydroxybenzophenone and chloroacetyl chloride are reacted to obtain an ultraviolet absorption monomer, and both ends of the ultraviolet absorption monomer contain acyl chloride groups. The aminated titanium dioxide is polymerized through the amino groups on the surface and the acyl chloride groups and R-1,1'-di-2-naphthylamino groups at both ends of the ultraviolet absorption monomer to form a polymer with an o-hydroxybenzophenone structure on the surface of the titanium dioxide. The hydroxyl group and the carbonyl group in the o-hydroxybenzophenone structure can form a chelate ring structure. Under the irradiation of ultraviolet rays, the molecule undergoes thermal vibration, the chelate ring opens, and the light energy is converted into heat energy, thereby achieving the effect of absorbing ultraviolet rays and resisting ultraviolet aging;

[0026] Finally, the modified epoxy resin, modified titanium dioxide nanosheets, expanded clay sand, defoaming agent, leveling agent, curing agent and diluent are mixed to prepare an anti-slip and wear-resistant coating. The expanded clay sand in the coating has a rough surface, which can increase the friction of the contact surface, thereby improving the anti-slip performance and giving the coating anti-slip properties. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0028] The epoxy resin model used in all the following embodiments and comparative examples is E20; the particle size of the ceramsite sand is 250-380 μm; the defoamer model is DC-65; the leveling agent model is BYK307; the curing agent model is BANCO-905; the diluent is acetone; the coating substrate of the applicator is tinplate, and the coating thickness is 80 μm.

[0029] Example 1

[0030] A non-slip and wear-resistant coating, the preparation method is as follows:

[0031] (1) Weighing epoxy resin and vinyl diphenylphosphine in a mass ratio of 1:0.3, mixing epoxy resin and propylene glycol methyl ether in a mass ratio of 1:1.8 at 110° C. for 5 min to obtain solution A, mixing vinyl diphenylphosphine, azobisisobutyronitrile, and propylene glycol methyl ether in a mass ratio of 1:0.06:2 to obtain solution B, and adding solution B dropwise to solution A at a dropping rate of 1 mL / min. After the addition is completed, the temperature is raised to 115° C. and the reaction is continued for 4 h, then the temperature is lowered to 80° C., epichlorohydrin in an amount of 0.3 times the mass of vinyl diphenylphosphine is added and the reaction is continued for 4 h, and the propylene glycol methyl ether is removed by vacuum rotary evaporation to obtain a modified epoxy resin;

[0032] (2) Weigh 2,2',4,4'-tetrahydroxybenzophenone and chloroacetyl chloride in a molar ratio of 1:2, mix chloroacetyl chloride and tetrahydrofuran in a mass ratio of 1:20 to obtain a chloroacetyl chloride solution, mix 2,2',4,4'-tetrahydroxybenzophenone, triethylamine and tetrahydrofuran in a mass ratio of 1:0.7:20, and then dropwise add the chloroacetyl chloride solution at 8°C at a rate of 0.6 mL / min. After the dropwise addition is completed, continue to react at 8°C for 6 hours. After the reaction is completed, add an ice-water mixture of 80 times the mass of 2,2',4,4'-tetrahydroxybenzophenone, filter, wash 4 times with a saturated sodium bicarbonate solution, and dry at room temperature for 12 hours to obtain an ultraviolet absorbing monomer;

[0033] (3) Tetrabutyl titanate and 36 wt % hydrofluoric acid solution were mixed in a volume ratio of 1:0.12, reacted in a high pressure reactor at 180° C. for 24 h, cooled to room temperature after the reaction, washed with 0.1 mol / L sodium hydroxide solution and pure water three times respectively, dried at 80° C. for 6 h, calcined in a muffle furnace at 400° C. for 2 h, and finally sieved through a 200 mesh sieve to obtain titanium dioxide nanosheets, titanium dioxide nanosheets, 3-aminopropyl-trimethoxysilane, and anhydrous ethanol in a mass ratio of 1:0.5 :50, stirred at 50°C for 8h, filtered and washed with pure water for 4 times, dried at 60°C for 8h to obtain amino titanium dioxide nanosheets, amino titanium dioxide nanosheets, R-1,1'-bi-2-naphthylamine, ultraviolet absorption monomer, triethylamine, N,N-dimethylformamide were mixed in a mass ratio of 1:1.5:1.7:0.5:40, heated to 95°C, reacted for 5h, cooled to room temperature, filtered, washed with pure water for 4 times, and dried at 60°C for 12h to obtain modified titanium dioxide nanosheets;

[0034] (4) Weigh the following components by mass: 100 parts of modified epoxy resin, 3 parts of modified titanium dioxide nanosheets, 2 parts of expanded clay sand, 1 part of defoaming agent, 1 part of leveling agent, 22 parts of curing agent, and 30 parts of diluent, mix the above components evenly, and apply them on the surface of the substrate using an applicator. Bake at 80°C for 30 minutes, then increase the temperature to 120°C and bake for 30 minutes to obtain a non-slip and wear-resistant coating.

[0035] Example 2

[0036] A non-slip and wear-resistant coating, the preparation method is as follows:

[0037] (1) Weighing epoxy resin and vinyl diphenylphosphine in a mass ratio of 1:0.35, mixing epoxy resin and propylene glycol methyl ether in a mass ratio of 1:1.9 at 110° C. for 4 min to obtain solution A, mixing vinyl diphenylphosphine, azobisisobutyronitrile, and propylene glycol methyl ether in a mass ratio of 1:0.07:2.5 to obtain solution B, and adding solution B dropwise to solution A at a dropping rate of 1 mL / min. After the addition is completed, the temperature is raised to 115° C. and the reaction is continued for 3.5 h. The temperature is lowered to 75° C., epichlorohydrin in an amount of 0.35 times the mass of vinyl diphenylphosphine is added and the reaction is continued for 3.5 h. The propylene glycol methyl ether is removed by vacuum rotary evaporation to obtain a modified epoxy resin;

[0038] (2) Weigh 2,2',4,4'-tetrahydroxybenzophenone and chloroacetyl chloride in a molar ratio of 1:2, mix chloroacetyl chloride and tetrahydrofuran in a mass ratio of 1:25 to obtain a chloroacetyl chloride solution, mix 2,2',4,4'-tetrahydroxybenzophenone, triethylamine and tetrahydrofuran in a mass ratio of 1:0.8:25, and then dropwise add the chloroacetyl chloride solution at 6°C at a rate of 0.6 mL / min. After the dropwise addition is completed, continue to react at 6°C for 5.5 hours. After the reaction is completed, add an ice-water mixture with a mass of 90 times that of 2,2',4,4'-tetrahydroxybenzophenone, filter, wash with a saturated sodium bicarbonate solution three times, and dry at room temperature for 11 hours to obtain an ultraviolet absorbing monomer;

[0039] (3) Tetrabutyl titanate and 36 wt % hydrofluoric acid solution were mixed in a volume ratio of 1:0.13, reacted in a high pressure reactor at 180° C. for 24 h, cooled to room temperature after the reaction, washed with 0.1 mol / L sodium hydroxide solution and pure water three times respectively, dried at 80° C. for 5 h, calcined in a muffle furnace at 400° C. for 2 h, and finally passed through a 200 mesh sieve to obtain titanium dioxide nanosheets, titanium dioxide nanosheets, 3-aminopropyl-trimethoxysilane, and anhydrous ethanol in a mass ratio of 1:0.6: 55, stirred at 45 ° C for 7 hours, filtered and washed with pure water for 3 times, dried at 60 ° C for 7 hours to obtain amino titanium dioxide nanosheets, amino titanium dioxide nanosheets, R-1,1'-bi-2-naphthylamine, ultraviolet absorption monomer, triethylamine, N,N-dimethylformamide were mixed in a mass ratio of 1:1.7:1.8:0.6:45, heated to 93 ° C, reacted for 4.5 hours, cooled to room temperature, filtered, washed with pure water for 3 times, and dried at 60 ° C for 11 hours to obtain modified titanium dioxide nanosheets;

[0040] (4) Weigh the following components by mass: 100 parts of modified epoxy resin, 3.5 parts of modified titanium dioxide nanosheets, 2.5 parts of expanded clay sand, 1.5 parts of defoaming agent, 1.5 parts of leveling agent, 23 parts of curing agent, and 33 parts of diluent, mix the above components evenly, and apply them on the surface of the substrate using an applicator. Bake at 80°C for 30 minutes, then increase the temperature to 120°C and bake for 30 minutes to obtain a non-slip and wear-resistant coating.

[0041] Example 3

[0042] A non-slip and wear-resistant coating, the preparation method is as follows:

[0043] (1) Weighing epoxy resin and vinyl diphenylphosphine in a mass ratio of 1:0.4, mixing epoxy resin and propylene glycol methyl ether in a mass ratio of 1:2.0 at 110° C. for 3 min to obtain solution A, mixing vinyl diphenylphosphine, azobisisobutyronitrile, and propylene glycol methyl ether in a mass ratio of 1:0.08:3 to obtain solution B, and adding solution B dropwise to solution A at a dropping rate of 1 mL / min. After the addition is completed, the temperature is raised to 115° C. and the reaction is continued for 3 h. The temperature is lowered to 70° C., epichlorohydrin in an amount of 0.4 times the mass of vinyl diphenylphosphine is added and the reaction is continued for 3 h. The propylene glycol methyl ether is removed by vacuum rotary evaporation to obtain a modified epoxy resin;

[0044] (2) Weigh 2,2',4,4'-tetrahydroxybenzophenone and chloroacetyl chloride in a molar ratio of 1:2, mix chloroacetyl chloride and tetrahydrofuran in a mass ratio of 1:30 to obtain a chloroacetyl chloride solution, mix 2,2',4,4'-tetrahydroxybenzophenone, triethylamine and tetrahydrofuran in a mass ratio of 1:0.9:30, and then dropwise add the chloroacetyl chloride solution at 4°C at a rate of 0.6 mL / min. After the dropwise addition is completed, continue to react at 4°C for 5 hours. After the reaction is completed, add an ice-water mixture with a mass of 100 times that of 2,2',4,4'-tetrahydroxybenzophenone, filter, wash with a saturated sodium bicarbonate solution 3 times, and dry at room temperature for 10 hours to obtain an ultraviolet absorbing monomer;

[0045] (3) Tetrabutyl titanate and 36 wt% hydrofluoric acid solution were mixed in a volume ratio of 1:0.14, reacted at 180°C for 24 h in a high pressure reactor, cooled to room temperature after the reaction, washed with 0.1 mol / L sodium hydroxide solution and pure water three times respectively, dried at 80°C for 4 h, calcined in a muffle furnace at 400°C for 2 h, and finally passed through a 200 mesh sieve to obtain titanium dioxide nanosheets, titanium dioxide nanosheets, 3-aminopropyl-trimethoxysilane, and anhydrous ethanol in a mass ratio of 1:0. The mixture was stirred at 40°C for 6 hours, filtered, washed with pure water for 3 times, and dried at 60°C for 6 hours to obtain amino titanium dioxide nanosheets; the amino titanium dioxide nanosheets, R-1,1'-bi-2-naphthylamine, ultraviolet absorption monomer, triethylamine, and N,N-dimethylformamide were mixed in a mass ratio of 1:2:1.9:0.7:50, heated to 90°C, reacted for 4 hours, cooled to room temperature, filtered, washed with pure water for 3 times, and dried at 60°C for 10 hours to obtain modified titanium dioxide nanosheets;

[0046] (4) Weigh the following components by mass: 100 parts of modified epoxy resin, 4 parts of modified titanium dioxide nanosheets, 3 parts of expanded clay sand, 2 parts of defoaming agent, 2 parts of leveling agent, 24 parts of curing agent, and 35 parts of diluent, mix the above components evenly, and apply them on the surface of the substrate using an applicator. Bake at 80°C for 30 minutes, then increase the temperature to 120°C and bake for 30 minutes to obtain a non-slip and wear-resistant coating.

[0047] Comparative Example 1

[0048] The difference between Comparative Example 1 and Example 2 is that step (1) is not included, and step (4) is modified to weigh the following components by mass: 100 parts of epoxy resin, 3.5 parts of modified titanium dioxide nanosheets, 2.5 parts of expanded clay sand, 1.5 parts of defoaming agent, 1.5 parts of leveling agent, 23 parts of curing agent, and 33 parts of diluent. The above components are mixed and applied to the surface of the substrate using an applicator, baked at 80°C for 30 minutes, then heated to 120°C and baked for 30 minutes to obtain an anti-slip and wear-resistant coating.

[0049] Comparative Example 2

[0050] The difference between Comparative Example 2 and Example 2 is that step (1) is modified as follows: epoxy resin and vinyl diphenylphosphine are weighed in a mass ratio of 1:0.35, epoxy resin and propylene glycol methyl ether are mixed in a mass ratio of 1:1.9 at 110°C for 4 min to obtain solution A, vinyl diphenylphosphine, azobisisobutyronitrile and propylene glycol methyl ether are mixed in a mass ratio of 1:0.07:2.5 to obtain solution B, solution B is added dropwise to solution A at a dropping rate of 1 mL / min, the temperature is raised to 115°C after the addition is completed, the reaction is continued for 3.5 h, the temperature is lowered to 75°C, propylene glycol methyl ether is removed by vacuum rotary evaporation to obtain a modified epoxy resin.

[0051] Comparative Example 3

[0052] The difference between Comparative Example 3 and Example 2 is that step (3) is modified as follows: tetrabutyl titanate and 36 wt % hydrofluoric acid solution are mixed in a volume ratio of 1:0.13, reacted in a high pressure reactor at 180 ° C for 24 h, cooled to room temperature after the reaction, washed with 0.1 mol / L sodium hydroxide solution and pure water three times each, dried at 80 ° C for 5 h, and then placed in a muffle furnace at 400 ° C for calcination for 2 h, and finally passed through a 200 mesh sieve to obtain titanium dioxide nanosheets, titanium dioxide nanosheets, 3-aminopropyl-trimethoxysilane, and anhydrous ethanol in a mass ratio of 1:0.6:55 were mixed, stirred at 45 ° C for 7 h, filtered and washed with pure water three times, and dried at 60 ° C for 7 h to obtain modified titanium dioxide nanosheets.

[0053] Comparative Example 4

[0054] The difference between Comparative Example 4 and Example 2 is that step (3) is not included, and step (4) is modified as follows: the following components are weighed in parts by mass: 100 parts of modified epoxy resin, 2.5 parts of expanded clay sand, 1.5 parts of defoaming agent, 1.5 parts of leveling agent, 23 parts of curing agent, and 33 parts of diluent, the above components are mixed evenly, and applied to the surface of the substrate using an applicator, baked at 80°C for 30 minutes, then heated to 120°C and baked for 30 minutes to obtain a non-slip and wear-resistant coating.

[0055] Test Example 1

[0056] Flame retardant performance test

[0057] Test method: According to the standard GB / T2406.2-2009, the limiting oxygen index of the anti-skid and wear-resistant coatings prepared in each embodiment and comparative example was tested using a limiting oxygen index instrument. The results are shown in Table 1.

[0058] Table 1

[0059] Limiting oxygen index (%) Limiting oxygen index (%) Example 1 31.43 Comparative Example 1 22.73 Example 2 30.61 Comparative Example 2 31.36 Example 3 32.02 Comparative Example 3 31.69 Comparative Example 4 27.96

[0060] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 1, it can be found that the anti-skid and wear-resistant coating prepared by the present invention has good flame retardant properties.

[0061] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Example 1, indicating that the epoxy resin is grafted with vinyl diphenyl phosphine and then reacted with epichlorohydrin to obtain a modified epoxy resin, and the carbon-carbon double bond on the vinyl diphenyl phosphine is grafted to the side chain of the epoxy resin under the action of the initiator, thereby introducing a phosphorus element with a flame retardant function into the epoxy resin, thereby giving the coating flame retardant properties.

[0062] Test Example 2

[0063] Impact resistance test

[0064] Test method: According to the standard GB / T 1732-2020, the impact strength of the anti-slip and wear-resistant coatings prepared in the examples and comparative examples was tested using an impact tester. The results are shown in Table 2.

[0065] UV aging test

[0066] Test method: The anti-skid and wear-resistant coatings prepared in the embodiments and comparative examples were placed in a UV aging box for irradiation. The temperature in the aging box was 50°C, the irradiation time was 720h, the wavelength of the ultraviolet light was 340nm, the light power was 40W, and the distance between the coating and the light source was 50mm. The impact strength of the coating before and after UV aging was tested according to the test method for impact resistance, and the change rate W was calculated. The calculation formula of W is: W=(W0-W1) / W0*100%; W0 is the impact strength before UV aging, and W1 is the impact strength after UV aging; the results are shown in Table 2.

[0067] Table 2

[0068] <![CDATA[Impact strength (kg*J / cm 2 )]]> Impact strength change rate (%) Example 1 24.36 2.83 Example 2 23.54 2.76 Example 3 24.11 3.09 Comparative Example 1 22.14 3.45 Comparative Example 2 23.07 3.37 Comparative Example 3 21.75 43.24 Comparative Example 4 16.64 59.36

[0069] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 2, it can be found that the anti-skid and wear-resistant coating prepared by the present invention has good impact resistance and UV aging resistance.

[0070] By comparison, the impact strength of Examples 1 to 3 is greater than that of Comparative Example 4, and the change rate of the impact strength of Examples 1 to 3 is less than that of Comparative Examples 3 and 4, indicating that the use of a silane coupling agent allows the surface of the titanium dioxide nanosheet to carry amino groups. Titanium dioxide, as a rigid particle, has a higher hardness and stronger wear resistance, which can improve the wear resistance and impact resistance of the coating. For the coating used outdoors, it can reflect ultraviolet rays to achieve a certain anti-ultraviolet aging function; 2,2',4,4'-tetrahydroxybenzophenone and The ultraviolet absorbing monomer is prepared by the reaction of chloroacetyl chloride. The two ends of the ultraviolet absorbing monomer contain acyl chloride groups. The aminated titanium dioxide is polymerized through the amino groups on the surface and the acyl chloride groups and R-1,1'-di-2-naphthylamino groups at both ends of the ultraviolet absorbing monomer to form a polymer with an o-hydroxybenzophenone structure on the surface of the titanium dioxide. The hydroxyl and carbonyl groups in the o-hydroxybenzophenone structure can form a chelate ring structure. Under the irradiation of ultraviolet rays, the molecules undergo thermal vibrations, the chelate ring opens, and the light energy is converted into heat energy, thereby achieving the effect of absorbing ultraviolet rays and resisting ultraviolet aging.

[0071] Test Example 3

[0072] Antimicrobial performance testing

[0073] Test method: The antibacterial rate of the anti-skid and wear-resistant coatings prepared in the examples and comparative examples was measured according to the standard GB / T 21866-2008, and the bacterial species was Staphylococcus aureus. The results are shown in Table 3.

[0074] Table 3

[0075]

[0076]

[0077] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 3, it can be found that the anti-skid and wear-resistant coating prepared by the present invention has good antibacterial properties.

[0078] By comparison, the antibacterial rates of Examples 1 to 3 are better than those of Comparative Examples 1 and 2, indicating that epichlorohydrin can not only increase the epoxy group content of the epoxy resin by reacting with phosphorus, but also convert vinyl diphenylphosphine into a quaternary phosphonium salt structure. The quaternary phosphonium salt molecules can penetrate the cell membrane of bacteria or molds and destroy the structure of the cell membrane, thereby inhibiting or killing microorganisms. Therefore, the presence of the quaternary phosphonium salt structure can give the coating certain antibacterial properties.

[0079] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A non-slip and wear-resistant coating, characterized in that: The anti-skid and wear-resistant coating is obtained by coating and curing. The anti-skid and wear-resistant coating mainly comprises: 100 parts by mass of modified epoxy resin, 3-4 parts by mass of modified titanium dioxide nanosheets, 2-3 parts by mass of ceramsite sand, 1-2 parts by mass of defoamer, 1-2 parts by mass of leveling agent, 22-24 parts by mass of curing agent, and 30-35 parts by mass of diluent; The modified epoxy resin is obtained by grafting vinyl diphenylphosphine onto epoxy resin and then reacting with epichlorohydrin; The modified titanium dioxide nanosheet is obtained by reacting amino titanium dioxide nanosheet, R-1,1'-bi-2-naphthylamine and ultraviolet absorption monomer; the ultraviolet absorption monomer is obtained by reacting 2,2',4,4'-tetrahydroxybenzophenone and chloroacetyl chloride.

2. A method for preparing an anti-skid and wear-resistant coating, characterized in that: The method comprises the following preparation steps: (1) weighing epoxy resin and vinyl diphenylphosphine in a mass ratio of 1:(0.3-0.4), mixing epoxy resin and propylene glycol methyl ether in a mass ratio of 1:(1.8-2.0) at 110° C. for 3-5 minutes to obtain solution A, mixing vinyl diphenylphosphine, azobisisobutyronitrile, and propylene glycol methyl ether in a mass ratio of 1:(0.06-0.08):(2-3) to obtain solution B, and adding solution B dropwise to solution A at a dropping rate of 1 mL / min. After the addition is completed, the temperature is raised to 115° C., and the reaction is continued for 3-4 hours. The temperature is lowered to 70-80° C., epichlorohydrin in an amount of 0.3-0.4 times the mass of vinyl diphenylphosphine is added, and the reaction is continued for 3-4 hours. The propylene glycol methyl ether is removed by vacuum rotary evaporation to obtain a modified epoxy resin; (2) Weighing 2,2',4,4'-tetrahydroxybenzophenone and chloroacetyl chloride in a molar ratio of 1:2, mixing chloroacetyl chloride and tetrahydrofuran in a mass ratio of 1:(20-30) to obtain a chloroacetyl chloride solution, mixing 2,2',4,4'-tetrahydroxybenzophenone, triethylamine, and tetrahydrofuran in a mass ratio of 1:(0.7-0.9):(20-30), and then dropping the chloroacetyl chloride solution at 4-8° C. at a dropping rate of 0.6 mL / min. After the dropwise addition is completed, continuing to react at 4-8° C. for 5-6 hours. After the reaction is completed, adding an ice-water mixture of 80-100 times the mass of 2,2',4,4'-tetrahydroxybenzophenone, filtering, washing with a saturated sodium bicarbonate solution for 3-4 times, and drying at room temperature for 10-12 hours to obtain an ultraviolet absorbing monomer; (3) mixing aminated titanium dioxide nanosheets, R-1,1'-bi-2-naphthylamine, ultraviolet absorption monomer, triethylamine, and N,N-dimethylformamide in a mass ratio of 1:(1.5-2):(1.7-1.9):(0.5-0.7):(40-50), heating to 90-95°C, reacting for 4-5 hours, cooling to room temperature, filtering, washing with pure water for 3-4 times, and drying at 60°C for 10-12 hours to obtain modified titanium dioxide nanosheets; (4) Weigh the following components by mass: 100 parts of modified epoxy resin, 3-4 parts of modified titanium dioxide nanosheets, 2-3 parts of expanded clay sand, 1-2 parts of defoaming agent, 1-2 parts of leveling agent, 22-24 parts of curing agent, and 30-35 parts of diluent, mix the above components evenly, and apply them on the surface of the substrate using an applicator to obtain a non-slip and wear-resistant coating after curing.

3. The method for preparing a non-slip and wear-resistant coating according to claim 2, characterized in that: The preparation method of the amino titanium dioxide nanosheets in step (3) is as follows: tetrabutyl titanate and 36wt% hydrofluoric acid solution are mixed in a volume ratio of 1:(0.12-0.14), reacted in a high-pressure reactor at 180°C for 24h, cooled to room temperature after the reaction, washed with 0.1mol / L sodium hydroxide solution and pure water three times respectively, dried at 80°C for 4-6h, calcined in a muffle furnace at 400°C for 2h, and finally sieved through a 200-mesh sieve to obtain titanium dioxide nanosheets, titanium dioxide nanosheets, 3-aminopropyl-trimethoxysilane, and anhydrous ethanol in a mass ratio of 1:(0.5-0.7):(50-60), stirred at 40-50°C for 6-8h, filtered and washed with pure water 3-4 times, and dried at 60°C for 6-8h to obtain amino titanium dioxide nanosheets.

4. The method for preparing a non-slip and wear-resistant coating according to claim 2, characterized in that: The curing conditions of step (4) are: baking at 80°C for 30 minutes, then heating to 120°C and baking for 30 minutes.

5. The method for preparing a non-slip and wear-resistant coating according to claim 2, characterized in that: The coating thickness of the coater in step (4) is 80 μm.

6. The method for preparing a non-slip and wear-resistant coating according to claim 2, characterized in that: The epoxy resin model in step (1) is E20.

7. The method for preparing a non-slip and wear-resistant coating according to claim 2, characterized in that: In step (4), the particle size of the ceramsite sand is 250-380 μm; the defoaming agent model is DC-65; the leveling agent model is BYK307; the curing agent model is BANCO-905; and the diluent is acetone.

8. Use of the anti-slip and wear-resistant coating prepared by the method for preparing the anti-slip and wear-resistant coating according to any one of claims 1 to 7 in a basketball court.

Citation Information

Patent Citations

  • Efficient thick copper plate solder resist printing method

    CN114206018A

  • Corrosion-resistant heat-dissipating protective coating and preparation method thereof

    CN114539876A

  • Preparation of silicon dioxide modified polyethylene material and application of silicon dioxide modified polyethylene material in insulated cable

    CN115651298A

  • Preparation method of vinyl anticorrosive resin coating

    CN117925057A

  • Environment-friendly fireproof wear-resistant silicon glaze floor material and preparation process thereof

    CN117986968A

Cited By

  • Anti-ultraviolet epoxy resin coating and preparation method thereof

    CN120944429A